1992
DOI: 10.1901/jaba.1992.25-217
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Safety Skills to High School Students With Moderate Disabilities

Abstract: Teaching students with disabilities to respond appropriately to potentially dangerous situations is a useful skill that has received little research attention. This investigation taught 3 students with moderate mental retardation to remove and discard broken materials (plates, glasses) safely from (a) a sink containing dishwater, (b) a countertop, and (c) a floor. A 4th student was instructed on the sink task only. A multicomponent treatment package was used to teach the skills. Simulated materials were used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 11 publications
0
26
0
1
Order By: Relevance
“…Of the 10 reports on CTD, there were 4 treatment packages that combined time delay with other instructional procedures (Dipipi, Jitendra, & Miller, 2001;Gardill & Browder, 1995;Morse & Schuster, 2000;Winterling, Gast, Wolery, & Farmer, 1992), and one comparison of CTD with the system of least prompts (Ault, Wolery, Gast, Doyle, & Eizenstat, 1988). Three of the twelve studies compared the effectiveness of the PTD procedure with other instructional procedures, including the system of least prompts strategy (Godby, Gast, & Wolery, 1987), a visual fading procedure (Matson, Sevin, Box, Francis, & Sevin, 1993), and the most-to-least instructional strategy (Heckaman, Alber, Hooper, & Heward, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 10 reports on CTD, there were 4 treatment packages that combined time delay with other instructional procedures (Dipipi, Jitendra, & Miller, 2001;Gardill & Browder, 1995;Morse & Schuster, 2000;Winterling, Gast, Wolery, & Farmer, 1992), and one comparison of CTD with the system of least prompts (Ault, Wolery, Gast, Doyle, & Eizenstat, 1988). Three of the twelve studies compared the effectiveness of the PTD procedure with other instructional procedures, including the system of least prompts strategy (Godby, Gast, & Wolery, 1987), a visual fading procedure (Matson, Sevin, Box, Francis, & Sevin, 1993), and the most-to-least instructional strategy (Heckaman, Alber, Hooper, & Heward, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Winterling et al (1992) did not specify which of the four participants was identified with ASD, so data from this study are presented separately under each analyzed variable, since we know that at least one of the participants was diagnosed with ASD or autistic-like behaviors. From the 16 participants, 10 were male and 5 were female.…”
Section: Ctd Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The barriers identified for individuals with disabilities included safety and skill deficits, two areas that may benefit from targeted skills training. There is a great deal of behavior analytic research demonstrating the effectiveness of available methods to teach self-help and safety skills (e.g., Bannerman et al 1991;Batu et al 2004;Taylor et al 2004;Winterling et al 1992). We recommend that practitioners consult previous research to guide their intervention efforts and focus on training the necessary skills and safety behaviors that improve an individual's ability to live independently, as appropriate.…”
Section: Implications For Behavior Analystsmentioning
confidence: 99%